2014
DOI: 10.1177/0047237915579886
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Prevention and School Students

Abstract: The Drug Education in Victorian Schools program provided integrated education about licit and illicit drugs, employed a harm minimization approach that incorporated participatory, critical thinking and skill-based teaching methods, and engaged parental influence through home activities. A cluster-randomized, controlled trial of the program was conducted with a student cohort during Year 8 (13 years) and Year 9 (14 years). Twenty-one secondary schools in Victoria, Australia, were randomly allocated to the Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…Previous studies have found a relationship between a decrease in substance use and an increase in life satisfaction. Social-emotional learning competencies is also effective in reducing substance abuse (Midford et al 2014;2018) and suicidal ideation (Gravesteijn et al 2011). The fact that social-emotional learning competencies reduces substance abuse is consistent with the finding that social-emotional learning competencies has an effect on life satisfaction obtained as a result of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have found a relationship between a decrease in substance use and an increase in life satisfaction. Social-emotional learning competencies is also effective in reducing substance abuse (Midford et al 2014;2018) and suicidal ideation (Gravesteijn et al 2011). The fact that social-emotional learning competencies reduces substance abuse is consistent with the finding that social-emotional learning competencies has an effect on life satisfaction obtained as a result of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Some educational interventions were described in more than one article. In such cases, the records were merged and assessed as one study [ 16 , 17 , 56 , 70 72 , 119 ]. The most common study design was cluster randomized (25 articles, 22%) and quasi-experimental (20 articles, 17%).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, research conducted in Australia concerned such health topics as psychoactive substance use [ 70 72 , 81 ], lifestyle [ 16 , 17 ], as well as public [ 23 , 102 ] and mental health [ 23 ], while an educational intervention conducted in South America covered the topic of SRH [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Primary prevention programs provided by [INSERT name of school] will promote abstinence. They will also include, for older students, some harm minimization components such as practical knowledge and skills to enable young people to have a safety plan and to enable safer decisions regarding drug use (McBride et al, 2004;McKay et al, 2014;Midford et al, 2018;Midford et al, 2015;Newton et al, 2010;Vogl et al, 2009).…”
Section: Primary Preventionmentioning
confidence: 99%